2001
DOI: 10.1016/s0304-3959(00)00380-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life differs among headache diagnoses: analysis of SF-36 survey in 901 headache patients

Abstract: This paper presents the results of health-related quality of life (HRQoL) in 901 patients consecutively visiting a headache clinic of a national medical center in Taipei, Taiwan. HRQoL was evaluated with the Medical Outcome Study-Short Form (SF-36) and the Hospital Anxiety and Depression Scale (HADS). According to the classification criteria for chronic daily headache (CDH) proposed by Silberstein et al. (Neurology 47 (1996) 871) five hundred and ninety-three (66%) patients had CDH, of whom transformed migrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
145
6
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(187 citation statements)
references
References 18 publications
32
145
6
4
Order By: Relevance
“…Wang et al [21] evaluated HRQoL in 901 patients who visited a headache clinic by using the Medical Outcomes Study short form health survey (SF-36) and the hospital anxiety and depression scale (HADS). They compared HRQoL in 193 patients with episodic migraine and in 541 patients with chronic daily headache (CDH).…”
Section: Hrqol Differs Among Headache Diagnosesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [21] evaluated HRQoL in 901 patients who visited a headache clinic by using the Medical Outcomes Study short form health survey (SF-36) and the hospital anxiety and depression scale (HADS). They compared HRQoL in 193 patients with episodic migraine and in 541 patients with chronic daily headache (CDH).…”
Section: Hrqol Differs Among Headache Diagnosesmentioning
confidence: 99%
“…Compared with CTTH patients, TM patients scored significantly lower on all SF-36 scales except for PF and RE. Wang et al [21] concluded that the SF-36 scores in patients with CDH depended on the percentage of the type of patients in the sample: the greater the proportion of TM patients, the more impaired the SF-36 scores were.…”
Section: Hrqol Differs Among Headache Diagnosesmentioning
confidence: 99%
“…HRQOL measurement tools communicate the impact of illness on the patient's well-being, providing unique insight into the evaluation and management of migraine. Previous studies have indicated significant reductions in HRQOL among subjects with migraine [5][6][7][8][9][10]. Despite the episodic nature of migraine, HRQOL has been shown to be comparable to living with chronic diseases such as diabetes and arthritis [5].…”
mentioning
confidence: 99%
“…The administered questionnaire evaluated effect of the disease on well-being and functional status by asking patients to selfrate 36 items that measured 8 health domains, and a single item that measured changes in self-perceived health. 16 The SF-36 is one of the most widely used physical and mental health status instruments and is increasingly being used for measuring outcomes in patients with pain. 17,18 It has established reliability and validity in chronic pain disorders, [19][20][21] and it includes 8 health concepts: (1) limitations on physical activities because of health problems, (2) limitations on social activities because of physical or emotional problems, (3) limitations on usual role activities because of physical health problems, (4) bodily pain, (5) general mental health (psychologic distress and well-being), (6) limitations on usual role activities because of emotional problems, (7) vitality (energy and fatigue), and (8) general health perceptions.…”
Section: Outcome Measurementsmentioning
confidence: 99%